THE EFFECT OF INTERPERSONAL & PSYCHOLOGICAL CAPITAL COMMUNICATION ON EMPLOYEE PERFORMANCE (CASE STUDY AT PT. BANK DEF) - Yudi Susworo (Universitas Trisakti, 2017)
The research objectives include, first, to analyze the effect of interpersonal communication on employee performance, second. To analyze the influence of psychological capital on employee performance, third. To analyze the influence of interpersonal communication and psychological capital on employee performanceIn this study, researchers used sampling techniques, while the population was all clerical / staff and officer level employees spread across 5 main offices and branches in the Jabodetabek area, the total questionnaire distributed was 200 respondents with the criteria being clerical / staff and officers who were not serving as unit, department or division leader. With a minimum work period of 1 monthThe results of this study researchers found a significant and positive influence between interpersonal communication variables on performance variables. There is a psychological capital effect on employee performance. Psychological capital makes employees committed to high performance. Leadership interpersonal communication and psychological capital together have an influence on employee performance.